Gastric histopathological features after the administration of omeprazole, amoxicillin, and clarithromycin in gastritis Helicobacter pylori rat model - Yulizal, OK; Tarigan, Setia Budi; Isnainul, OK; Muttaqin, Zainul (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This research work aimed to assess the histopathological features and degree of gastritis severity in a rat model, induced by Helicobacter pylori infection after administering omeprazole, amoxicillin, and clarithromycin as the standard first-line eradication regimen. Material and Methods: Twenty-one male rats were adapted for 7 days and randomly divided into three equal groups. Group 1 was considered a negative control. Group 2 and Group 3 were treated as H. pylori-inoculated groups. Group 2 was set as a positive control. Group 3 was administered omeprazole, amoxicillin, and clarithromycin as a first-line eradication regimen. Gastric histopathological examination was conducted. The difference in the severity of gastritis among the groups was examined using the one-way analysis of variance test. The significance was determined to be p < 0.05. Results: Gastritis was found in all inoculated groups. The severity of gastritis was highest in Group 2 (p < 0.05). We could see a refinement in gastritis severity after administering omeprazole, amoxicillin, and clarithromycin as a first-line eradication regimen (Group 3 vs. Group 2; p <0.05). Conclusion: Gastritis, induced by the H. pylori rat model, was found in all inoculated groups. There was a refinement in the degree of gastritis severity after the administration of omeprazole, amoxicillin, and clarithromycin as a first-line eradication regimen. J. Adv. Vet. Anim. Res., 8(1): 158-163, Mar 2021 http://doi.org/10.5455/javar.2021.h498